Fluoroquinolones in the management of tuberculous meningitis: Systematic review and meta-analysis. Issue 4 (October 2018) - Rizvi, Imran; Malhotra, Hardeep Singh; Garg, Ravindra Kumar; Kumar, Neeraj; Uniyal, Ravi; Pandey, Shweta
Highlights: Data on use of fluoroquinolones in tuberculous meningitis is sparse. Routine addition of fluoroquinolones to standard regimen cannot be recommended. Substitution of a standard drug for fluoroquinolone, similarly, is not advisable. Multi-centric randomized controlled trials are required to address deficits. Summary: Objectives: Tuberculous meningitis carries a high rate of mortality and morbidity despite of an adequate treatment. Newer agents are being searched to improve outcome of these patients. Fluoroquinolones might be useful in the management of tuberculous meningitis in view of good cerebrospinal fluid penetration and good in-vitro activity against the mycobacterium. This review summarizes the effects of fluoroquinolone in first line regimens in tuberculous meningitis. Methods: A systematic search of literature was performed using PubMed, Cochrane Central Register of Controlled Trials (CENTRAL) and LILACS for articles published till march 2017. We also searched meta-register of controlled trials and bibliography of relevant studies. Randomized controlled trials (RCTs) where a fluoroquinolone was administered in addition or substitution of standard antituberculosis drugs formed the basis of selection criteria. Data was extracted on a pre-specified format. Risk ratio (RR) for dichotomous data was calculated and fixed effect model was used to combined the data if no heterogeneity was found. Death was taken as the primary outcome measure. Results: Five trials including 1115 patients of tuberclous meningitis were included. Addition of a fluoroquinolone to a standard regimen was not found to significantly reduce mortality [RR = 0.68 (0.30–1.52)] (low-quality evidence). Addition of a fluoroquinolone to an intensified regimen (containing high dose rifampicin) was not found to significantly reduce mortality [RR = 0.97 (0.78–1.20)] (low-quality evidence). Substitution of fluoroquinolone for ethambutol [RR = 1.17 (0.67–2.07)] (moderate-quality evidence, risk of harm cannot be ruled out) or for rifampicin [RR = 0.57 (0.32–1.01)] (low-quality evidence) in the standard regimen in terms of mortality did not show any benefit. There was no significant difference in the distribution of overall adverse events except for a higher incidence of vision loss and seizures in the fluoroquinolone arm. Conclusion: Routine addition or substitution of a fluroquinolone in the standard regimen can not be recommended at present. As most of the evidence driven in this review was of moderate- to low-quality, further research in this area is expected to make a significant impact in formulating a directive.